The Disclosure of Sharia Non-Compliance Income: Comparative Study between Full-fledged and Subsidiaries Malaysian Islamic Banks - Atharyanshah Puneri; Moustapha Chora; Nazarov Ilhamiddin; Hafiz Benraheem (JESI (Jurnal Ekonomi Syariah Indonesia), 2019)
The purpose of this paper is to analyze to what extend Islamic banks in Malaysia practice disclosure regarding Sharia non-compliant income. Furthermore, this paper also investigates how bank distribute the Sharia non-compliant income. This paper acquires qualitative approach. The qualitative approach is adopted by doinga document analysisabout the literatures from previous studies that the Sharia non-compliant income.Based on the data collected, Bank Islam clearly and properly discloses its Sharia non-compliance income and we recommend any other Islamic banks to follow it. Also, the study find out that does not matter whether they are full-fledge or subsidiaries, the practice is quite the same.